DYNAMICS OF SUBJECTIVE WELL-BEING IN INITIATORS OF THE (NON-PROFIT) MOVEMENT "SEDEKAH MAINAN" - Su'ad Jauharoh; Maratul Jannah Umbola (Ittishal Educational Research Journal, 2025)
Subjective Well-being (SWB) relates to how a person evaluates their overall life positively. Income is one of the predictors of SWB, which allows a person to have a greater ability to achieve some goals. However, the fact is that there are also people who can achieve SWB without looking at the material element, namely volunteers (volunteers) who sincerely do activities without material rewards. One of the volunteering that is still actively running and has been widely discussed in the media is the (non-profit) movement "Sedekah Mainan". This mini-research aims to find out how the dynamics (causes, existing conditions, and impacts) of SWB in volunteers who initiate the (non-profit) Sedekah Mainan movement. This study was conducted using a case study approach. Data collection techniques used interviews with the main subject (founder/ initiator) and significant other (co-founder) as a form of data triangulation and observation. The results of this mini research reveal that engaging in activities that are in accordance with mission and passion is a major factor in achieving SWB (eudemonic perspective). The subject found his life mission and passion in this Toy Alms movement. In addition, the subject also has positive affect and life satisfaction that is more dominant than negative affect which makes the subject achieve SWB (hedonic aspect perspective).